Rapid high resolution imaging with a dual-channel scanning technique - de Castro, Alberto; Huang, Gang; Sawides, Lucie; Luo, Ting; Burns, Stephen A (Optics letters, 2016)
A spatial shift between channels in a dual-beam raster-scan imaging system introduces a temporal separation between images from the two channels that can be much shorter than the frame rate of the system. The technique is demonstrated by measuring the velocity of erythrocytes in the retinal capillaries. We used an adaptive optics scanning laser ophthalmoscope and introduced a temporal separation between imaging channels of 4.7 ms. We imaged three subjects and measured changing capillary blood flow velocity at the pulse rate. Since the time shift between channels is easily and continuously adjustable, this method can be used to measure rapidly changing events in any raster scan system with little added complexity.